MANAGEMENT OF ANESTRUS AND SUBESTRUS COWS USING HORMONALANDNON ORMONALDRUGS. - KUMAR, RAJESH; BUTANI, M G; DHAMI, A J; KAVANI, F S; SHAH, R J; KILLEDAR, ANKITA (The Indian Journal of Animal Reproduction, 2011)
A total of 57 anestrus/subestrus crossbred cows were divide._in to three treatment groups, each of 13, 13 and 23 cows, keeping 8 cows as untreated control. Thirteen true anestrus cows were treated with nutritional supplements for 15 days and another 13 with single dose of GnRH 20 μg i/m, while 23 subestrus cows were treated with single dose of PGF 2a 500 μg i/m. Animals detectti"d irf strus were inseminated artificially. The estrus induction response for the 3 groups was 76.92, 84.62 and 91 .30 %, with the mean interval of 26. 70±4.52, 28.27±6.46 and 3.52±0.46 days (P<0.01 ), respectively. The estrus response (50 % ) and estrus interval (48.25±10.80 days) of untreated control group were significantly (P<0.05) lower as compared to all treatment groups. Of the responded cows, 70.00, 72.73 and 71.43 % conceived within 3 cycles as again t 50 % conception in control group. The conception rates at induced estrus in 3 groups were 40.00, 18.18 and 52.38 %, respectively.